Alternative Procedure for One-Stage Nostril Reconstruction: A Case Report - Iswinarno D. Saputro; Heri Noviana (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Closure of nasal defect remains a challenge for surgeons. There are several ways to do nasal reconstruction, including donor site for nasal reconstruction due to its vascularity that is superior to other areas. Methods: This is a case report of a 75-year old male patient with Squamous Cell Carcinoma on his left nostril who underwent wide excision. This action left a 4-cm defect, whilst the nasal septum remained intact. This defect closure was using V-Y advancement full thickness nasolabial flap in one step. This defect closure was using V-Y advancement full thickness nasolabial flap in one step. Results: The defect closure was performed with tum over local (nasobialis) flap from the left side of the nasal cartilage. The superiority of this flap, it is able to be performed bulking, so that closure with turn over local nasolabial flap has been a sole option in nostril reconstruction for decades, which gave very good cosmetic results. After being followed for 1 month after surgery, the flap was viable, the contour was well formed, the scar was minimal, and there was no respiratory disruption. The patient was satisfied by the results. Conclusion: Nasolabial turn over local flap can be used as an option to close a relatively wide nostril